A Coupled Regulation and Flexible Ramp Product Marginal Pricing Rule - Chavez-Orostica, H; Lismayes-Aguilar, A (Institute of Electrical and Electronics Engineers Inc., 2021)
The high integration levels of non-dispatchable generation have necessitated more efficient formulations to cope with the increasing requirements for operating reserves and ramping capability. One aspect that has captured particular attention is the representation of opportunity costs derived from flexibility constraints, in order to propose efficient pricing rules for regulating reserves and flexible ramp products. In this work, a price rule for regulating reserves and flexible ramp products is proposed as a function of the opportunity cost and the available ramp capacity of the units. An example considering the IEEE RTS 24-Bus System is presented to show numerical results. © 2021 IEEE.